New Bird Records for Nusa Tenggara Islands: Sumbawa, Moyo, Sumba, Flores, Pulau Besar and Timor - Trainor, Colin R; Benstead, Phil J; Martin, Keith; Lesmana, Dwi; Agista, Dian; Benstead, M Charlotte; Drijvers, Raf; Setiawan, Iwan (KUKILA, 2006)
We present a total of 59 new island records comprising more than 100 independent site records of 52 species for selected Nusa Tenggara islands: Sumbawa (21) and its satellite Moyo (18); Sumba (4); Flores (3) and its satellite islands including Pulau Besar (12); and Timor (3). Records were gathered between 1994 and 2001 during surveys by BirdLife international Indonesia Programme, Dames and Moore Pry Ltd (especially within the Batu Hijau Project Area), and an extended bird watching visit. Records of particular note include those of the globally vulnerable Flores Green Pigeon Treron Jloris and two near-threatened species: Beach Thick-knee Esacus neglectus and Great-billed Heron Ardea sumatrana. A Superb Fruit-dove Ptilinopus superbus on Sumba represents the first record for Nusa Tenggara. Significant records of Palearctic migrants are accumulating for the region. We document the first two Nusa Tenggara records of the migrant Grey-streaked Flycatcher Muscicapa griseisticta and numerous records of Chinese Sparrowhawk Accipiter soloensis and Japanese Sparrowhawk A. gularis.